2001
DOI: 10.1097/00043764-200112000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Factor Analysis, Clinical Findings, and Functional Status in a Population-Based Case Control Study of Gulf WarUnexplained Illness

Abstract: Few epidemiological studies have been conducted that have incorporated clinical evaluations of Gulf War veterans with unexplained health symptoms and healthy controls. We conducted a mail survey of 2022 Gulf War veterans residing in the northwest United States and clinical examinations on a subset of 443 responders who seemed to have unexplained health symptoms or were healthy. Few clinical differences were found between cases and controls. The most frequent unexplained symptoms were cognitive/psychological, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 0 publications
5
30
0
Order By: Relevance
“…Neumann et al [39] analyzed the characteristics of FMS in men and showed that, compared to women, men reported more severe symptoms, decreased PF, and a lower quality of life. On the other hand, a follow-up study of patients who sustained neck injuries following a motor vehicle accident and developed FMS showed that men were less likely than women to remain fibromyalgic 3 years after the event (11% vs. 100%, respectively) [40].…”
Section: Discussionmentioning
confidence: 99%
“…Neumann et al [39] analyzed the characteristics of FMS in men and showed that, compared to women, men reported more severe symptoms, decreased PF, and a lower quality of life. On the other hand, a follow-up study of patients who sustained neck injuries following a motor vehicle accident and developed FMS showed that men were less likely than women to remain fibromyalgic 3 years after the event (11% vs. 100%, respectively) [40].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of individual diagnoses within the broad diagnostic categories of hospitalizations significantly associated with response focused on the five most frequent three-digit diagnostic codes to examine their association with response. Additionally, specific ICD-9-CM diagnoses that have previously been indicative of chronic multisymptom illness were explored [14][15][16][17][18][19][20][21][22][23][24][25]. To further evaluate health care usage differences between responders and nonresponders, the mean number of days spent hospitalized or in outpatient care during the year prior to enrollment was also compared.…”
Section: Health Care Datamentioning
confidence: 99%
“…Nearly 10% of deployed American troops returned home with a host of medically unexplained symptoms-primarily fatigue, musculoskeletal achiness, and cognitive dysfunction. In a survey of healthcare-seeking GVs, we found that 16.1% reported symptoms consistent with CFS (77) and that, on careful clinical evaluation, many fulfilled the published case definition for CFS (42); finding CFS as a common diagnosis in symptomatic GVs has been reported by others, as well (78). The problem with linking toxic factors with CFS is that veterans did not suffer symptoms of acute exposure to such factors.…”
Section: Environmental Causesmentioning
confidence: 68%